Kampen om sammenhængskraften - En analyse af begrebet sammenhængskraft i den offentlige debat fra 1994 til 2010 - Peters, Rikke Alberg (Slagmark - Tidsskrift for idéhistorie, 2018)
This article addresses the Danish concept ‘sammenhængskraft’ (social cohesion) in its shifting articulations in the Danish public debate from 1994-2010. By combining a discursive analytical approach with Reinhart Koselleck’s notion of asymmetric counterconcepts it is demonstrated how the concept is embedded in various political discourses. Through this process, which is described as a semantic battle, it gradually changes its meaning from an open social political concept used in particular when discussing future socio political challenges in the well fare state to a national conservative – and defensive – key concept. It is argued that when used in a political conflict as a conceptual tool with which to fight the enemy the term ‘sammenhængskraft’ creates disintegration rather than cohesion.